Modeling and Stability analysis of proposed Wind Farm at Búrfell, Iceland - Arshad, Abdul Rehman, 1990- (2015)
Wind energy is clean and renewable source of energy and it’s impact on the nature is as minimum as compared to other sources of energy. There is a lot of potential available in Iceland ready to be exploited. A wind turbine generator system consists of various components. Each component is modeled and extensively studied. It is found that the turbine inertia and stiffness play a great role in wind turbine torque stability. Since the wind speed is not uniform, therefore, the available power is also not constant. The frequency of AC also depends on the generator speed and it needs to be constant when the generator is connected to the power grid which is not possible in variable speed generator system. This problem is resolved by using rectifier and inverter. Rectifier converts AC into DC. Rectifier also controls the amount of power extracted from the turbine. It is necessary to maintain the smooth operation of the turbine. Therefore, rectifier controller is used. Rectifier controller ensures the smooth operation of wind turbine by controlling the extraction of power and maintain the DC voltages. This is achieved by controlling the power extraction using Park Transformation[20] with PI controller. Inverter converts AC into DC. It controls the power flow to the grid by controlling the output frequency and ensures to maintain the DC voltages. It also eliminated the interfacing problem with power grid as it generates the AC voltage of frequency compatible to the power grid. It is accomplished by Inverter control unit. Inverter control unit controls the flow of power from DC bus to the power grid by controlling frequency. This is achieved by Park Transformation[20] with PI controller. To ensure the unidirectional flow of power, a diode is used at DC bus. The WTGS takes some time initially to build up the voltages and once enough torque and speed is achieved it runs smoothly. In stability point of view, based on extensive simulation, the WTGS has proven to be stable even under faulty conditions.